Modality in the campaign speech of Republic Korea presidential candidate Moon Jae In (문제인) in 2017 - Dinar Asri; Risa Triarisanti; Didi Sukyadi (Journal of Korean Applied Linguistics, 2021)
Speech is a form of expressing thoughts in the form of words addressed to many people. In a speech, the speaker usually expresses one’s attitude or assessment toward someone, as called modality. This study discussed the modalities contained in the campaign speech of presidential candidate, Moon Jae In, at the presidential election of the Republic of Korea in 2017. Through this speech, Moon Jae In could win the hearts of the Republic of Korea people and win the election in 2017. The theory used in this research was the modality theory, proposed by Sun Hye Ok (2016). This study used descriptive qualitative methods, namely reporting and assessing the linguistic data through modality theory as an analytical tool. The results of the analysis showed that there were 63 forms of modality in it. There were 6 forms 명제양태 (proposition modality) and 57 forms 사건양태 (event modality). The percentage of data 명제양태 (prediction modality) was 10% and 사건양태 (event modality) was 90%, so it could be said that in his speech, Moon Jae In revealed more forms of disclosure for the future. Those forms were evidenced through sentences that contain abilities, musts, and goals for the future.